Recommended best management practices for Pagosa bladderpod (Physaria pruinosa): practices to reduce the impacts of road maintenance activities to plants of concern - Panjabi, Susan, author; Smith, Gabrielle, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2017)
Pagosa bladderpod (Physaria pruinosa = Lesquerella pruinosa) is a small, rosette-forming, yellow-flowered plant in the Brassicaceae (Mustard Family) that is known only from two counties in southern Colorado and one county in northern New Mexico. This species is considered to be imperiled at a global and state level (G2/S2); Colorado Natural Heritage Program 2017). One of the biggest conservation issues for this imperiled plant species is the lack of awareness of its existence and status. Avoiding or minimizing impacts to this species during road maintenance activities will effectively help to conserve its habitat and is unlikely to confer substantial impacts on road maintenance goals and projects. The Best Management Practices (BMPs) included in this document are intended to help increase the awareness of this species for anyone involved in road maintenance activities.
Prepared for: the Colorado Natural Areas Program.
June 2017.
Keywords: Pagosa bladderpod; road maintenance impact; special management areas; noxious weed management; roadside plants